POLITIK HUKUM PERENCANAAN PROGRAM LEGISLASI NASIONAL DI INDONESIA - Muslimah Muslimah (AkMen JURNAL ILMIAH, 2015)
National legislative program as instruments for drafting legislation is one important element in the development of the legal framework, particularly in the context of legal materials (legal substance) .it Law-making starting from planning, through national legislation program. Therefore the national legislation program is expected to guide and control the preparation of legislation mengikt all competent institutions shape. Thus the importance of the national legislation program in the order of formation of the legislation, since the enactment of Law No. 10 of 2004 and the kemudaian replaced by Law No. 12 of 2011, the national legislation is set to be one of the conditions or processes that must be passed in the establishment of laws OF. It can be seen in the sound of article 16 of Law No. 12 of 2011 which confirms that the planning of lawmaking be done in the national legislation